TRANSLATION CHALLENGES RELATED TO VOCABULARY ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article delves into the lexical problems of translation, exploring thechallenges translators face when bridging the linguistic and cultural gaps betweenlanguages. It highlights specific issues such as non-equivalence, polysemy, idiomaticexpressions, cultural-specific terms, and false friends. By examining these challenges,